Improving Students' Reading Comprehension Skills through the Implementation of Project-Based Learning Models and Learning Motivation - Tenni; Slamet, St Y; Adi, Fadhil Purnama; Christy Suryandari, Kartika (International Journal of Elementary Education, 2025)
Low reading ability is caused by a lack of effectiveness in using innovative learning models. For students who have low abilities, this will have a negative impact in the future. This study aims to analyze the influence of the Project-Based Learning (PjBL) model and learning motivation on the reading comprehension ability of grade V elementary school students. The research method used was a pseudo-experiment with a pretest-posttest control group design. The research sample was taken using the purposive sampling technique consisting of 37 students in the experimental group and 37 students in the control group. The data collection technique in this study uses test results, namely pretest and postest. The data analysis techniques include descriptive and inferential statistics with hypothesis testing using an independent t-test. The results showed that the average post-test score in the experimental group was 84.19, while in the control group it was 78.46. The results of the hypothesis test showed that the p-value was 0.0010 < 0.05, which indicated that there was a significant difference in reading comprehension skills between students in the experimental group and the control group. Based on the results of the study, it can be concluded that the Project-Based Learning (PjBL) model has a significant influence on the reading comprehension skills of grade V elementary school students. The implications of this study show that the use of the PjBL model in learning can be an effective strategy to improve students' reading comprehension skills in elementary school.